Modernity, Postmodernity, and Transgression in Sábato's Esthetics: Poetic Dissemination, Defeat of Utopias, Returning Bodies - María Rosa Lojo (Studies in 20th & 21st Century Literature, 2005)
After defining the problematic term "Postmodernity" and its possible application to Latin America, the position of Ernesto Sábato as an essayist and narrator is discussed in light of Modernity (questioned by him as the rationalist and enlightened canon, but applauded as romantic and surrealistic rebellion), and Postmodernity with which it connects from diverse axis: the poetic of desire and that of transgression (vanguard movements related to Foucault, Bataille and Derrida), the theory of reality as "fragment" and "simulacrum" and the suppression of oppositions in the paroxysm of "symbolic exchange." Sábato would transcend from the central proposition of his writing, the vertigo of reproduction, the chain of copies, to plunge his hero in the sacrificial experience of the dissemination that reestablishes the broken ties between the realities of life and death. In his narrative the esthetic and metaphysical, avant-garde project triumphs in the "symbolic exchange" although a space remains for the Utopian construction of a new society. In his last novel the political project of other vanguard movements sink in an exacerbated violence that reproduces over the victims of torture (the "disappeared"), the planetary catastrophe of the Cloaca. In this novel the failure of Modernity is produced as a philosophical and political project, another "disappearance," that of the writer himself. He will be estranged, alienated from the shapeless, unclassifiable body of the novel next to the unburied body of the other disappeared who wait for their reintegration in the material and symbolic space of mother earth, and in the virtual space of common memory.
Keywords: modernity; modern; postmodernity; postmodern; utopia; Ernesto Sábato; rationalism; poetry; reality; fragmentation; life; death; violence; philosophy; memory; mother earth; poetic dissemination; esthetics